1982
DOI: 10.1002/hed.2890050106
|View full text |Cite
|
Sign up to set email alerts
|

Verrucous carcinoma of the oral cavity

Abstract: Since verrucous carcinoma was first identified as a distinct clinicopathologic entity, a great deal of confusion has developed in interpreting the proper criteria for diagnosis. Various authors, therefore, have developed considerably different concepts of the features that make this lesion a unique variant of squamous cell carcinoma. Consequently, there is great confusion in the literature as to the appropriate therapeutic approach, the incidence of recurrence, and the frequency of anaplastic transformation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Another study involving 30 cases of laryngeal VC also showed that surgery is the optimal therapy but that radiation and even chemotherapy can be used as alternatives for inoperable cases [20]. Although the older literature raised the issue of radiotherapy-related anaplastic or malignant transformation in VC [3,9,[21][22][23][24][25], this has clearly been refuted. Radiotherapy is now an accepted treatment modality for inoperable VC or for patients who are poor surgical candidates [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Another study involving 30 cases of laryngeal VC also showed that surgery is the optimal therapy but that radiation and even chemotherapy can be used as alternatives for inoperable cases [20]. Although the older literature raised the issue of radiotherapy-related anaplastic or malignant transformation in VC [3,9,[21][22][23][24][25], this has clearly been refuted. Radiotherapy is now an accepted treatment modality for inoperable VC or for patients who are poor surgical candidates [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Verrucous carcinoma is a rare variant of squamous cell carcinoma that presents in the head and neck with the most common sites being the oral cavity and larynx [1][2][3][4][5][6][7][8]. It is so uncommon, in fact, that verrucous carcinoma composes only 5% of tumors at these sites [2,14].…”
Section: Introductionmentioning
confidence: 99%
“…Some oral verrucous carcinomas may be associated with small outbreaks of EC (16,25,26) or regional lymphatic metastases (27,28). In one study (26), it was observed that 21 out of 104 oral verrucous carcinomas had poorly differentiated EC outbreaks.…”
Section: Investigationsmentioning
confidence: 99%